Higher Spins, Strings and Dualities - Francia, Dario; Klebanov, Igor; Gaberdiel, Matthias; Sagnotti, Augusto; Sorokin, Dmitri; Vasiliev, Mikhail (Il Colle di Galileo, 2014)
This workshop program brought together experts and young researchers from all over the world with the aim of fostering exchange on a number of topics that lie at the interface between String Theory, considered to be a promising candidate for a unified theory of fundamental interactions, and the theory of higher-spin fields. Key problems addressed included issues related to the roots of String Theory, the AdS/CFT correspondence, the underlying higher spin geometry and symmetries, the consistency of interacting Higher Spin Field Theory, black holes, modern trends in classical and quantum gravity and other topics.